Immune responses in the uterine mucosa: clues for vaccine development in pigs - Choudhary, Pooja; Magloire, Donaldson; Hamonic, Glenn; Wilson, Heather L. (Frontiers in Immunology, 2023)
The immune system in the upper reproductive tract (URT) protects against sexually transmitted pathogens, while at the same time providing immune tolerance responses against allogenic sperm and the developing fetus. The uterine environment is also responsive to hormonal variations during the estrus cycle, although the most likely timing of exposure to pathogens is during estrus and breeding when the cervix is semi-permissive. The goal for intrauterine immunization would be to induce local or systemic immunity and/or to promote colostral/lactogenic immunity that will passively protect suckling offspring. The developing fetus is not the vaccine target. This minireview article focuses on the immune response induced in the pig uterus (uterine body and uterine horns) with some comparative references to other livestock species, mice, and humans.